AB1063 A Survey of Musculoskeletal Ultrasound (MSUS) Training amongst Rheumatologists and Trainees across Wales. (15th July 2016) - Sheikh, F.; Humphreys, E.; Lim, V.; Choy, E.; Chitale, S.
Abstract : Background: Although MSUS is routinely used in rheumatology practice, expertise in performing MSUS and training opportunities vary considerably across UK and Europe. [1, 2, 3] There is a growing consensus to include MSUS in the UK Rheumatology curriculum. The All Wales Rheumatology Ultrasound group (AWRUG) conducted a preliminary survey of rheumatologists across Wales in 2013 and based on this survey, developed a modular MSUS training programme to improve training facilities and access to mentorship.[4] In August 2015, AWRUG re-surveyed rheumatologists across Wales, seeking their feedback and views on MSUS training. This 2 year follow on survey depicts the current state of Rheumatology MSUS training and expertise in Wales. Objectives: 1. To ascertain the level of MSUS expertise and interest following the modular MSUS training programme. 2. To ascertain the opinion of rheumatology consultants and trainees as to whether MSUS training should be part of the Rheumatology curriculum in the UK. Methods: An online survey link was sent to all rheumatologists in Wales by email in August 2015, asking for their feedback on the AWRUG delivered MSUS training and about their expertise in MSUS. Results: Out of 32 respondents including 9 trainees and 21 consultants, 14 (44%) had access to US mentorship and training facilities. 11 (34%) respondents had no MSUS training and 2 (6%) were expert/ trainers. 13 (41%) could identify synovitis/ erosions on MSUS. 18 (56%) attended an AWRUG MSUS masterclass (with 11 finding it useful and 7 very useful). 17 (53%) were using MSUS routinely in their clinical practice, mostly requesting scans for synovitis or shoulder pathology. 27 (85%) felt that MSUS should be included in the rheumatology curriculum; however 3 (33%) trainees and 2 (9%) consultants felt that it should not be included. 13 (41%) felt that theoretical knowledge of MSUS plus scanning for synovitis should be mandatory. Regarding service provision, 20 (62%) felt that Routine MSUS should be provided by radiology department whereas 11 (34%) felt that rheumatologists should also offer this. Most respondents felt that MSUS for synovitis should be provided by rheumatologists wholly 9 (28%) or in collaboration with radiology 15 (47%). Conclusions: 1. All respondents who attended the AWRUG Masterclasses, found them useful, confirming the need for an ongoing regional training programme. 2. Most rheumatology consultants and two thirds of rheumatology trainees in Wales feel that MSUS training should be included in the rheumatology curriculum. References: Cunnington, Joanna, et al. Attitudes of United Kingdom rheumatologists to musculoskeletal ultrasound practice and training. Annals of the rheumatic diseases 66.10 (2007): 1381–1383. Garrood, Toby, and Philip Platt. Access to training in musculoskeletal ultrasound: a survey of UK rheumatology trainees. Rheumatology 49.2 (2010): 391. Naredo, Esperanza, et al. Current state of musculoskeletal ultrasound training and implementation in Europe: results of a survey of experts and scientific societies. Rheumatology 49.12 (2010): 2438–2443. Humphreys, Emyr, et al. 246. Development of a Modular-Based Ultrasound Training Programme for Rheumatologists and Allied Health Professionals in Wales. Rheumatology 54.suppl 1 (2015): i145-i145. Disclosure of Interest: None declared